Individual risk assessment for prenatal counseling in early‐onset growth‐restricted and small‐for‐gestational‐age fetuses. (6th November 2020) - Mendoza, Manel; Hurtado, Ivan; Bonacina, Erika; Garcia‐Manau, Pablo; Serrano, Berta; Tur, Helena; Rodo, Carlota; Maiz, Nerea; Carreras, Elena
Abstract: Introduction: Early‐onset fetal growth restriction and small‐for‐gestational age of fetuses lead to an increased risk of adverse pregnancy outcomes. Doppler abnormalities can predict the occurrence of complications in the short term, but normal fetal Doppler values at the time of diagnosis do not exclude their occurrence in the long term. The objective of this study was to investigate the capacity of a predictive model to assess individual risks for prenatal counseling at the time of diagnosis. Material and methods: This was a prospective observational study of singleton pregnancies with estimated fetal weight below the 10th centile between 20 +0 and 31 +6 weeks of gestational age. Placental growth factor (PlGF) and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) levels, estimated fetal weight centile, uterine artery pulsatility index, fetal Doppler and maternal risk factors for placental disease were assessed at the time of enrollment. The occurrence of adverse perinatal outcomes or the need for elective delivery at <30, <34 or <37 weeks was considered an adverse pregnancy outcomes. Univariable logistic regression analysis was used to examine the association between each predictive variable and the adverse outcomes. A multivariable logistic regression‐based model was constructed with the combination of all variables. An additional model without sFlt‐1/PlGF was also created. Both models, and the sFlt‐1/PlGF alone, were used to develop the different formulas to assess individual risks. Receiver operating characteristic curves were constructed to assess and compare their performance of screening. Results: Forty‐nine small‐for‐gestational‐age fetuses and 124 with fetal growth restriction were enrolled at a median gestational age of 23.6 weeks. Elective delivery was needed in 77 (44.5%) women at <37 weeks, 53 (30.6%) women at <34 weeks and 30 (17.3%) at <30 weeks. Adverse perinatal outcomes occurred in 81 (55.9%) pregnancies. When areas under the curve were compared among models, no statistically significant differences were observed between the model with sFlt‐1/PlGF and sFlt‐1/PlGF alone; however, the model without sFlt‐1/PlGF yielded an overall poorer performance. Conclusions: Individual risk assessment can be made at the time of early‐onset fetal growth restriction/small‐for‐gestational‐age diagnosis, which permits accurate counseling of parents with an affected fetus. Two formulas could be used: one combining maternal characteristics and ultrasound findings and the other with a single sFlt‐1/PlGF measurement.